PERILAKU HIDUP BERSIH DAN SEHAT RUMAH TANGGA DENGAN KEJADIAN DIARE PADA BALITA PINGGIRAN SUNGAI - Herawati; Safitri, Eka Saraditha; Rahmayanti, Devi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Diarrhea is one of symptom that causes death and has the highest morbidity rate in Indonesia,especially for children under five years of age. South Kalimantan in 2011 there were 66,765cases of diarrheal disease. One of the areas in South Kalimantan, namely the Banjar Regency in2010 to the highest regions of the occurrence of diarrheal disease with 3,077 cases. Diarrhea canbe prevented by application of a clean and health behavior order household. Research studies arecross-sectional correlation fringes of society river as much as 82 respondents in cluster samplingand measurement tools using a questionnaire. There are 82 respondent in total, the predominantresult was 42.7% of respondents have passable clean and healthy living behavior and 13.4% ofrespondents have bad clean and healthy living behaviour which is not dominant. The worse theimplementation of clean and healthy behavior of household, it will be easier for family membersin house for suffering diarrheal disease including the toddler.